Recovering the scandal of the cross : atonement in New Testament and contemporary contexts - Baker, Mark D. (Mark David), 1957-; Green, Joel B., 1956- (Downers Grove, Ill. : IVP Academic, 2011)
Since its publication in 2000, Recovering the Scandal of the Cross has initiated among evangelicals a new conversation about the nature of the atonement and how it should be expressed in the varied and global contexts of today. In this second edition Green and Baker have clarified and enlarged their argument in a way that will continue to provoke thought and conversation on this critical topic.
Making sense of the cross of Christ -- The cross and the New Testament : a melange of voices (part one) -- The cross and the New Testament : a melange of voices (part two) -- The saving significance of Jesus' death in the New Testament -- Models of the atonement : a history and assessment (part one) -- Models of the atonement : a history and assessment (part two) -- Removing alienating shame : the saving - significance of the cross in Japan -- Confounding evil through cunning and compassion -- Hearing other voices : exploring the ongoing significance of Jesus' death -- Communicating the atonement today.
Previous edition reversed authors.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Crucifixion; Atonement